Project manager success factors in managing green buildings in Malaysia : knowledge and skills / Asniza Hamimi Abdul Tharim ... [et al.] - Asniza Hamimi, Abdul Tharim; Aifa Syazwani, Zainudin; Nur’Ain, Ismail; Thuraiya, Mohd; NoorAileen, Ibrahim (2015)
Malaysia is very committed in moving towards a greener future and increasing the growth of sustainable construction and green development. Green development can reduce energy consumption, increase productivity and improve environmental wellbeing. However, the green construction approach often faces challenges in terms of the adoption of new processes and technologies. Therefore, skills and knowledge areas are essential in overcoming the challenges in green construction. The main objective of this paper is to identify the project manager’s success factors in terms of knowledge and skills in managing the green construction. Data were obtained by using questionnaire survey distributed among 103 (74%) Bumiputera developers in the Klang Valley and data was subsequently analyzed by using SPSS 20.0 to generate results. Survey outcome indicates that most project managers possess a good level of knowledge and skills in managing green construction in Malaysia. It is believed that when the project manager has a good level of knowledge and skills in the green area, it may help to reduce and overcome challenges during the construction of green projects.